2016
DOI: 10.4238/gmr.15048740
|View full text |Cite
|
Sign up to set email alerts
|

Role of ADH1B rs1229984 and ALDH2 rs671 gene polymorphisms in the development of Alzheimer's disease

Abstract: In the present study, we investigated the association between ADH1B rs1229984 and ALDH2 rs671 polymorphisms and the development of Alzheimer's disease in a Chinese population. Genotyping of the ADH1B rs1229984 and ALDH2 rs671 polymorphisms was carried out by polymerase chain reaction-restriction fragment length polymorphism. Logistic regression analyses revealed that the AA genotype of ADH1B rs1229984 was associated with an increased risk of Alzheimer's disease (OR = 2.54, 95%CI = 1.19-5.41). In addition, ADH1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 30 publications
3
14
0
Order By: Relevance
“…The accumulative analysis presented fluctuating findings and the results tending to show a potential association by Ma et al (29) (Figure 3 for A vs. G model, Supplementary Figure S2 for other models). A sensitivity analysis was conducted by removing each included study, and fluctuating results were observed after several studies were removed (Figure 4 for A vs. G model, Supplementary Figure S3 for other models).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The accumulative analysis presented fluctuating findings and the results tending to show a potential association by Ma et al (29) (Figure 3 for A vs. G model, Supplementary Figure S2 for other models). A sensitivity analysis was conducted by removing each included study, and fluctuating results were observed after several studies were removed (Figure 4 for A vs. G model, Supplementary Figure S3 for other models).…”
Section: Resultsmentioning
confidence: 87%
“…Finally, nine publications (11 independent studies) involving 2,283 patients and 3,032 controls were included (15, 2330). Three common SNPs were reported; eight studies focused on the rs671 G>A polymorphism (15, 2329), two studies focused on the rs4767944 C>T polymorphism (27, 30), and one study focused on the rs441 T>C polymorphism (27). In all included studies, most subjects were from East Asians countries including China, Japan, and Korea, except for one study that was performed in the Iranian population (30).…”
Section: Resultsmentioning
confidence: 99%
“…Several reports of genetic modifications, such as genome-wide association studies (GWAS) and single genetic association studies, have reported gene variation on ALDH2 in East Asian patients (Hao et al, 2011). In this respect, Ma et al (2016) investigated the association between ADH1B rs1229984 and ALDH2 rs671…”
Section: Molecular Alterationsmentioning
confidence: 99%
“…However, the actual mechanisms are unknown. The ALDH2 polymorphisms are related to Alzheimer's disease, which implies an association between ALDH2 polymorphisms and memory function [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ALDH2 polymorphisms are associated with the effects of alcohol on various neurophysiological and psychomotor functions [19,20]. All these studies [17][18][19][20] hypothesized that the ALDH2 gene polymorphisms affect aldehyde metabolism and cognitive function. We therefore hypothesize that the ALDH2 gene affects the cognitive functions in patients with OUD as it does in alcohol abusers, and that it leads to the underlying cognitive deficits in OUD.…”
Section: Introductionmentioning
confidence: 99%